A virtual classroom for enhancing English Language students’ intercultural competence during the internship period in Gaviota Tours Agency - Sánchez Fernández, Déborath; Hernández Cabrera, Ana Karla (Universidad Central "Marta Abreu" de Las Villas. Facultad de Humanidades. Departamento de Lengua Inglesa, 2021)
English language teachers should prepare students for contact with people from other cultures and effective intercultural communication. Therefore, it is desirable that foreign language teaching embraces not only the development of language skills, but also intercultural training. Specifically, students of the degree course English Language with a Second Foreign Language (French) at the Universidad Central “Marta Abreu” de Las Villas (UCLV) have some difficulties trying to attain intercultural competence to deal with the professional demands in the internship period in the tourist sector. This paper discusses an original research project in the area of Computer Assisted Language Learning (CALL) to enable intercultural competence through the syllabus renewal of English Language Degree Course towards an intercultural approach. It uses a qualitative research approach including some empirical methods to collect information. A virtual classroom of the subject Práctica Laboral is proposed and was published in the Moodle platform. Its design included a set of contents, digital tools and tasks selected and/or created to develop students intercultural skills and attitudes and to enhance students’ intercultural knowledge of the Canadian tourism. The proposal is intended for students to meet the professional profile demands and serve as an extended experience of virtual multicultural environment.
Diseño de un aula virtual para el desarrollo de competencia intercultural en los estudiantes de Lengua Inglesa durante la práctica profesional en Gaviota Tours
Keywords: Intercultural Communication; Intercultural Communicative Competence; Internship Period; Information and Communication Technologies; Distance Learning; Virtual Classroom; Lengua Inglesa